2020
DOI: 10.3892/mmr.2020.11104
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic postconditioning attenuates the inflammatory response in ischemia/reperfusion myocardium by upregulating miR‑499 and inhibiting TLR2 activation

Abstract: Toll-like receptor 2 (Tlr2)-mediated myocardial inflammation serves an important role in promoting myocardial ischemic/reperfusion (I/R) injury. Previous studies have shown that miR-499 is critical for cardioprotection after ischemic postconditioning (IPostC). Therefore, the present study evaluated the protective effect of IPostC on the myocardium by inhibiting TLR2, and also assessed the involvement of microRNA (miR)-499. Rat hearts were subjected to 30 min of ischemia and 2 h of reperfusion. The IPostC was 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Considering the results presented in Figure 3C , we observed decreased amounts of cytokines (CXCL1 and IL-6) in the PostC condition vs. IR, whereas Maruyama et al have reported similar values of coronary flow values at 60 min of reperfusion in both IR and PostC conditions ( 55 ). On the basis of these results, we can therefore suggest that the decrease in cytokine levels at IR60 observed after a PostC (see Figure 3C ) may result mainly from a decrease in the release of cytokines vs. IR, in accordance with the anti-inflammatory effect of PostC described in vivo ( 10 , 56 ). However, we cannot exclude an improvement in the coronary flow upon PostC, as described for many other cardioprotective strategies evaluated in our laboratory ( 53 , 54 ) or others ( 57 ), which could also contribute to the reduction in measured amounts of cytokines.…”
Section: Study Limitationsupporting
confidence: 81%
“…Considering the results presented in Figure 3C , we observed decreased amounts of cytokines (CXCL1 and IL-6) in the PostC condition vs. IR, whereas Maruyama et al have reported similar values of coronary flow values at 60 min of reperfusion in both IR and PostC conditions ( 55 ). On the basis of these results, we can therefore suggest that the decrease in cytokine levels at IR60 observed after a PostC (see Figure 3C ) may result mainly from a decrease in the release of cytokines vs. IR, in accordance with the anti-inflammatory effect of PostC described in vivo ( 10 , 56 ). However, we cannot exclude an improvement in the coronary flow upon PostC, as described for many other cardioprotective strategies evaluated in our laboratory ( 53 , 54 ) or others ( 57 ), which could also contribute to the reduction in measured amounts of cytokines.…”
Section: Study Limitationsupporting
confidence: 81%
“…Among which, autophagy has also been found to be involved in i/r (4). Studies have reported that ischemic postconditioning (iPostc) can protect the heart from i/r injury by transient intermittent i/r episodes prior to long-term ischemia or hypoxia reperfusion (5). Wei et al (6) found that iPostc could improve autonomic function in acute ischemic stroke patients through the enhancement of the total autonomic nerve activity and vagus nerve activity.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al (6) found that iPostc could improve autonomic function in acute ischemic stroke patients through the enhancement of the total autonomic nerve activity and vagus nerve activity. another study also found that iPostc attenuates the injury in i/r myocardium by upregulating microrna (mirna/mir)-499 and inhibiting Toll-like receptor 2 activation (5). mir-30a-5p, a member of the mir-30 family, is regarded as a key mirna in cardiovascular pathophysiology (7).…”
Section: Introductionmentioning
confidence: 99%
“…This protection may be achieved by the inhibition of TLR2 and the reduction of inflammatory cytokine release (including IL-1β and IL-6). These effects eventually lead to a dropping in the area of MI 26 . Therefore, regulating TLR2 signal may provide a new treatment strategy for heart failure.…”
Section: Discussionmentioning
confidence: 99%